Borrowings as source of lexical base forming in M. Hrushevsky’s social and political essays (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2014)
The article is devoted to investigation of lexical borrowings from Latin, German, Polish and Russian in M. Hrushevsky’s social and political essays; the analysis of semantic, structural and functional features of such borrowings are made and their stylistic status in the modern literary language is also determined.
Keywords: lexical borrowings; word-formative calquing; semantic calquing; Western Ukrainian literary language tradition